Strategi Pengembangan Usahatani Kopi di Kecamatan Modayag Kabupaten Bolaang Mongondow Timur - Saputro, Dio Reski; Indriani, Ria; Bakari, Yuliana (Fakultas Pertanian, Peternakan dan Perikanan Universitas Muhammadiyah Parepare, 2023)
Bolaang Mongondow Timur, as a coffee center in North Sulawesi, has played a role in contributing to coffee production. Modayag District, as the largest coffee-producing area and the largest land area in East Bolaang Mongondow Regency, has many obstacles to contribute to the achievement of coffee production. This research aims to discover the obstacles and strategies that can be done to develop coffee farming in Modayag District, East Bolaang Mongondow Regency. The analysis in this study is a qualitative descriptive analysis to determine the obstacles to the development of coffee farming and Process Hierarchy Analysis (AHP), which is used to determine strategies for developing coffee farming. The informants from this study were 12 key persons who were determined purposively to consist of related agencies, traders, and coffee farmers in the District of Modayag. The results showed that the obstacles in the development of coffee farming were the need for more information on cultivation techniques, the unavailability of post-harvest equipment, and the weak price protection and coffee quality assurance. With the AHP method, the results show that the policy aspect is the top priority, then the cultivation aspect, followed by the marketing aspect, the institutional aspect, and finally, the post-harvest processing aspect.